The association of diabetic retinopathy and diabetic kidney disease in patients with type 2 diabetes mellitus: a prospective observational research study - Wu, Yutong; Hong, Zhuomin; Luo, Xiangxia (Frontiers in Endocrinology, 2025)
BackgroundDiabetic retinopathy (DR) and diabetic kidney disease (DKD) are two prevalent diabetic complications significantly influencing global health and quality of life. However, little is known about their relationship in patients with type 2 diabetes mellitus (T2DM).AimThis study aimed to investigate the relationship between DR and DKD through a prospective observational research study.Patients and methodsT2DM patients were recruited from November 2020 to November 2022. A total of 223 T2DM patients were finally enrolled. Additionally, 50 healthy examinees were included as the control group. Diagnostic and staging criteria for DR are based on previously established standards. DKD was assessed using serum levels of cystatin C (CysC), β2-microglobulin (β2-MG), and homocysteine (Hcy). Traditional Chinese medicine (TCM) syndrome differentiation standards were based on the TCM Diagnosis and Treatment Standards for diabetes Retinopathy issued by the diabetes Branch of the Chinese Society of Traditional Chinese Medicine in 2011. The outcomes of interest were measured at baseline.ResultsThis study included 223 T2DM patients aged from 32 to 78 years. According to DR staging, patients were further categorized into four T2DM subgroups, namely, T2DM without DR, T2DM with light or moderate non-proliferative DR (lmNPDR), T2DM with heavy non-proliferative DR (hNPDR), and T2DM with proliferative DR (PDR). Among the participants, 154 (154/223, 69.06%) were diagnosed with DR. As DR severity increased, the levels of three DKD indicators presented a significant upward trend compared to those in the control group, except for Hcy in the PDR subgroup. Spearman’s correlation analysis revealed significant associations between each DKD indicator and the T2DM subgroups, with rs = 0.223, p = 0.001, for Hcy; rs = 0.452, p < 0.001, for CysC; and rs = 0.564, p < 0.001, for β2-MG. Three TCM syndrome types were identified in the 223 T2DM patients. For four T2DM subgroups, the proportion of qi–yin deficiency increased with decreasing DR severity, whereas the proportion of yin–yang deficiency increased with increasing DR severity. Three DKD indicators exhibited statistically significant differences between the deficiency of the liver and kidney or yin–yang deficiency and qi–yin deficiency, except for Hcy in yin–yang deficiency.ConclusionThis study suggests a potential association between DR and DKD and provides evidence that the incidence of qi–yin deficiency and yin–yang deficiency exhibits opposite trends with respect to DR severity.